Making Environmentally Friendly Handsoap using Anti-Microbial Strawberry as A Step in Preparing Independent Entrepreneurship for Students of SMAN 2 Rangkas Bitung - Handayani, Yenny Dwi; Mubarakah, Septyana; Nugraha, Gugun; Salsabila, Naila; Rachmadhani, Nabila (MOVE: Journal of Community Service and Engagement, 2025)
SMAN 2 Rangkas Bitung possesses significant potential, requiring support from various parties in its development. The purpose of this community service (PKM) activity is to equip students with applied science-based entrepreneurial skills through training in the production of environmentally friendly hand soap made from strawberries with antimicrobial properties. In addition to raising awareness of the importance of sanitation, this activity also aims to foster an entrepreneurial spirit from an early age by utilizing readily available local materials. The implementation method included counseling and education, product demonstrations, and practical and evaluation sessions. The outcome of this activity was the creation of an environmentally friendly hand soap product made from strawberries with natural antimicrobial properties. This product was produced through a series of practical activities that actively involved students, from the extraction of natural ingredients and the formulation of the soap solution to packaging and testing. Based on the evaluation results of the distributed questionnaires, the average understanding score for participants was 74 percent, indicating a positive response to the training. This activity demonstrates that collaboration between various parties can create simple yet impactful innovations for empowering the younger generation.